Moderation via Maqasid Al-Shariah: an analytical study - Ahmad Muhammad Husni,; Amir Husin Mohd Nor,; Ibnor Azli Ibrahim,; Abdel Wadoud Moustafa Moursi Elseoudi,; Hayatullah Laluddin,; Muhammad Adib Samsudin,; Anwar Fakhri Omar,; Muhammad Nazir Alias, (Institut Kajian Rantau Asia Barat, 2011)
This article deliberates on the best method for the formation of moderation in society in the light of the purposes of Syari’ah. It focuses on the aspects of the influence that represents the main objective in Islam, with reference to the five necessities. Allah s.w.t has commanded his servants to uphold justice and be steadfast and to avoid extremism and disintegration. Thus,there is no room for extremism and biasness in Syari’ah. For, it respects religious, cultural and civilization polarity and reject racism. Since human self is prone to desire, evil, amusement,demand for relaxation, hatred of hard work and at times overwhelmed by weakness, subjugating it to coercion and force, lead to its exhaustion and neglect. It is in the light of these facts that Islam granted to its adherents the right of relaxation and leisure to its adherents at a moderate level. Ironically, people with liberal set of mind tends to perceive religious conviction and moderation as extremism and radicalism hence, viewing permissiveness, disengagement with religion and morality as signs of progress and civilization. Moreover, they view religious adherence as a suppression of individual freedom and a hindrance to keeping abreast with civilization and progress. Therefore, Islam presented the best model for the organization of society and disciplining human behaviors and activities in the best manner possible, so as to lead a happy and prosperous life which is in harmony with human nature hence, dealing with contemporary issues specially those relating to Islamic thought effectively.